The Linkage of the Board of Directors and the Status of Aviation Industry Licensing Law - Ningrum, Lestari (STMT Trisakti, 2016)
Aviation business is a capital intensive and high risk in terms of safety. Legislation in force in Indonesia requires enterprises should cost in the form of a limited liability company that is obliged to deposit the basic capital of 500 billion rupiah. The capital cannot be made in working capital which is useful for the collateral to a third party. The regulations for a limited liability company are to be established by at least 2 people. The purpose of this research is to analyze the linkage of the board directors and the status of aviation industry licensing law. The position of the legal status of business entities where shareholder is only one person is to be studied in this descriptive study. The result shows that the airlines company should provide the capital risk and high insurance of the third party. UUPT also has given the authority of the shareholders (who owns 20 % of the share) to be decision makers in the company. However, without independent surveillance, it is possible that the shareholders do some mistakes in making decisions. Some mistakes are related to the policy, the using of authorized capital, and others. Keywords : limited liability company, business aviation, legal status.